THE RELATIONSHIP BETWEEN WORKLOAD AND FATIGUE LEVEL WITH ANXIETY LEVEL OF STUDENTS WHO ARE COLLEGE WHILE WORKING WHILE UNDERSTANDING ONLINE LEARNING METHODS IN STIKES PANTI RAPIH, YOGYAKARTA - Nosterisa Amora; Yulia Wardani; Bernadetta Eka Noviati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The COVID-19 disease causes many changes in aspects of life including education. Circular Letter Number 4 of 2020 concerning Implementation of Education Policy in Period Emergency Spread of COVID-19, where learning activities during a pandemic are carried out online or online which has advantages and disadvantages. This study aims to measure the levels of workload, fatigue and anxiety of students who work while studying while attending online lectures and examine the relationship between workload, fatigue level and anxiety levels. Researchers used quantitative descriptive correlative type research. The population of this study were 124 students using a purposive sampling technique to obtain 73 samples. Data collection methods are in the form of questionnaires from the Nasa Aeronautics and Space Administration Task Load Index (NASA-TLX), the Swedish Occupational Fatigue Inventory (SOFI) and the Hamilton Rating Scale for Anxiety (HARS). The statistical test used is the analysis of the Somer's D statistical test. The results showed that the level of workload, fatigue level and student anxiety level were in the moderate classification. The results of the correlation test showed that there was a significant relationship between fatigue level and anxiety level with a p value of 0.000 and a correlation coefficient of 0.495 with a positive relationship. Meanwhile, the workload variable with anxiety level and the workload variable with fatigue level did not find a significant relationship with p values of 0.484 and 0.540 respectively. This research recommends for students to be able to adapt and manage their time well while studying while working.